CAPITAL MARKET EFFICIENCY AND RETAIL INVESTOR RISK - Ahmad Yani; Aulia Saputra (Universitas Efarina, 2023)
This study aims to present a thorough analysis of the relationship between capital market efficiency and the risk faced by retail investors. Market efficiency is defined as the ability of the market to reflect all available information in asset prices, while retail investors' risk includes both systematic risk and idiosyncratic risk that they may experience. This study uses a theoretical framework that integrates the theories of market efficiency, investor behavior, and risk management. Market efficiency was also found to have a significant impact on the level of risk faced by retail investors. A more efficient market theoretically reduces the potential for arbitrage and increases transparency, but at the same time, can magnify market volatility. This research provides deep insight into how market efficiency and retail investor risk are intertwined and provides a basis for the development of adaptive investment strategies. Practical implications of the findings include the need for better financial education, emphasis on portfolio diversification, and increased investor awareness of the impact of market information on their investment behavior.